The Almost Sure Local Central Limit Theorem for the Negatively Associated Sequences - Yuanying Jiang; Qunying Wu (Journal of Applied Mathematics)
In this paper, the almost sure central limit theorem is established for sequences of negatively associated random variables: limn→∞(1/logn)∑k=1n(I(ak≤Sk<bk)/k)P(ak≤Sk<bk)=1, almost surely. This is the local almost sure central limit theorem for negatively associated sequences similar to results by Csáki et al. (1993). The results extend those on almost sure local central limit theorems from the i.i.d. case to the stationary negatively associated sequences.